Pembuatan bahan penyamak nano nabati dan aplikasinya dalam penyamakan kulit - Herminiwati, Herminiwati; Waskito, Sri; Purwanti, Christiana Maria Herry; Prayitno, Prayitno; Ningsih, Dwi (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2015)
This study aimed to create nano vegetable tanning materials of acacia bark extract. The process started with size reduction of acacia bark (16.7 mm x 4.9 mm x 1.8 mm), followed by counter current extraction of acacia bark with water at 80ºC with 1:3 bark to water ratio in order to obtain extracts with density of 9-10ºBe. Drying was done with a spray dryer. Particle size of the resulting powders was measured with particle size analyzer. Planetary ball mill was used for 6 hours to obtain average particle size of 72.9 nm. A variety of vegetable tanning materials were applied in the vegetable tanning process with varied concentrations of 15, 20, and 25%. The use of 25% nano vegetable tanning material of acacia bark extract gave the best results compared to liquid extract of acacia bark and mimosa. The properties of the leather obtained were tensile strength of 27.04 kg/cm2, elongation at break of 50%, shrinkage temperature of 84oC, and degree of tannage of 79.65%.Keywords: vegetable tanning material, nano particle, acacia bark, extraction, planetary ball mill.ABSTRAKPenelitian ini bertujuan untuk membuat bahan penyamak nano nabati dari ekstrak kulit kayu akasia. Proses pembuatannya dilakukan melalui tahapan pengecilan ukuran kulit kayu akasia (16,7 mm x 4,9 mm x 1,8 mm), dilanjutkan dengan ekstraksi kulit kayu akasia secara counter current menggunakan air 1:3 dengan suhu air awal 80ºC sehingga diperoleh ekstrak dengan densitas 9-10ºBe. Pengeringan dilakukan dengan spray dryer. Serbuk hasil spray dryer diukur partikelnya dengan particel size analyzer, kemudian diteruskan dengan pengecilan ukuran menggunakan planetary ball mill selama 6 jam sehingga diperoleh partikel berukuran rata-rata 72,9 nm. Berbagai bahan penyamak nabati diaplikasikan dalam proses penyamakan nabati pada kadar 15, 20, dan 25%. Penggunaan ekstrak nano nabati kulit kayu akasia sebesar 25% memberikan hasil terbaik dibanding ekstrak cair kulit kayu akasia maupun mimosa impor. Kulit tersamak yang dihasilkan memiliki kuat tarik sebesar 27,04 kg/cm2, kemuluran sebesar 50%, suhu kerut sebesar 84oC, dan derajat penyamakan sebesar 79,65%.Kata kunci: bahan penyamak nabati, partikel nano, kulit kayu akasia, ekstraksi, planetary ball mill.